1988
DOI: 10.1203/00006450-198808000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Maturation-Related Changes in Dopamine-Induced Relaxation of Isolated Rabbit Pulmonary Artery

Abstract: ABSTRACT. Studies were performed on isolated pulmonary arterial segments to investigate dopamine receptormediated relaxant effects at different times during development. Dopamine receptor-mediated relaxant effects can only be observed when vessels are precontracted with prostaglandin Fz, and in the presence of al, ag P, and serotonergic blockade. Helical strips of pulmonary arteries from rabbits of different ages (2, 7, 14, 30, and 90 days), partially precontracted by prostaglandin Fz, were tested for their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…Dopamine stimulates specific dopamine receptors at low concentration causing vasodilation, ␤ 1 -adrenoceptors at medium concentration, and ␣ 1 -adrenoceptors at high concentration (12). Evidence demonstrates that dopamine receptor activation may induce pulmonary vascular relaxation in various experimental models (23,29,30). However, our study fails to demonstrate any vasorelaxant effect at low-dose dopamine infusion in fetal pulmonary circulation.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Dopamine stimulates specific dopamine receptors at low concentration causing vasodilation, ␤ 1 -adrenoceptors at medium concentration, and ␣ 1 -adrenoceptors at high concentration (12). Evidence demonstrates that dopamine receptor activation may induce pulmonary vascular relaxation in various experimental models (23,29,30). However, our study fails to demonstrate any vasorelaxant effect at low-dose dopamine infusion in fetal pulmonary circulation.…”
Section: Discussioncontrasting
confidence: 74%
“…Thus the vascular response to norepinephrine may depend on the ratio of ␣ 1 -to ␣ 2 -and ␤-adrenoceptors at the surface of the endothelium or of the smooth muscle cells (40). Maturational change in pulmonary arterial adre-noceptors previously described may explain conflicting results regarding the vascular response to norepinephrine (3,23,30).…”
Section: Discussionmentioning
confidence: 99%
“…Radioligand binding and light microscopy techniques showed the existence of D 1 and D 2 receptors on the rabbit pulmonary artery [17] and only D 1 receptors rat renal artery. [18] As well, Mori et al [19] have been observed D 1 related vasodilation on rabbit pulmonary artery, which is reduced by cis-flupenthixol (nonselective D 1 receptor blocker) in an organ bath study. It was suggested that vascular effects of dopamine are produced by specific dopamine receptors in cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…D 1 receptors had also been detected in rabbit pulmonary artery. [19] Katai et al [25] have been reported that SCH 23390, a DA 1 receptor antagonist, decreased dopamine related vasodilation on ITA in an in-vitro study. In addition to, there are some studies reported that dopamine causes vasoconstriction on ITA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation